2017
DOI: 10.1007/s13562-017-0405-y
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic identification and expression analysis of the Malus domestica DREB2 transcription factors in different tissues and abiotic stress

Abstract: DREB transcription factors regulate the expression of many abiotic-stress-responsive genes and play critical roles in improving abiotic stress tolerance in plants.In this study, the MdDREB2 transcription factors in apple (Malus domestica) were identified through bioinformatics approach, and MdFREB2 transcript levels in different tissues and abiotic stress conditions were also further studied using RT-PCR methods. Fifteen MdDREB2 transcription factors were identified in apple genome, and all contain NLS motif a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Cold stress induces the expression of about 40% of drought-responsive rice genes ( Gao et al 2007 ). Overlap between the expression profiles of stress-responsive genes induced by drought and cold stress has been observed in apple ( Li et al 2017a ; Li et al 2019a ), tangerine ( Citrus) ( de Oliveira et al 2011 ), grape ( Vitis vinifera ) ( Zandkarimi et al 2015 ), Arabidopsis ( Arabidopsis thaliana ) ( Seki et al 2002 ), and other plant species. In addition, overexpression of genes encoding the transcription factor (TF) MYB121 in Malus ( Cao et al 2013 ), the antioxidant enzyme manganese superoxide dismutase (Mn-SOD) in Populus davidiana ( Populus ) ( Yu et al 2010 ), the trihelix TF family member cold-induced GT (poly [dG-dT] factor) (CIGT) from the wild tomato species Solanum habrochaites ( Yu et al 2018 ), and others improves plant tolerance to both drought and cold stresses.…”
Section: Introductionmentioning
confidence: 99%
“…Cold stress induces the expression of about 40% of drought-responsive rice genes ( Gao et al 2007 ). Overlap between the expression profiles of stress-responsive genes induced by drought and cold stress has been observed in apple ( Li et al 2017a ; Li et al 2019a ), tangerine ( Citrus) ( de Oliveira et al 2011 ), grape ( Vitis vinifera ) ( Zandkarimi et al 2015 ), Arabidopsis ( Arabidopsis thaliana ) ( Seki et al 2002 ), and other plant species. In addition, overexpression of genes encoding the transcription factor (TF) MYB121 in Malus ( Cao et al 2013 ), the antioxidant enzyme manganese superoxide dismutase (Mn-SOD) in Populus davidiana ( Populus ) ( Yu et al 2010 ), the trihelix TF family member cold-induced GT (poly [dG-dT] factor) (CIGT) from the wild tomato species Solanum habrochaites ( Yu et al 2018 ), and others improves plant tolerance to both drought and cold stresses.…”
Section: Introductionmentioning
confidence: 99%
“…The rootassociated bacteria are sensitive to even small changes in the pattern of compounds in the rhizosphere (Persello-Cartieaux et al, 2003), which may be altered by genetic modifications for enhancing or conferring specific traits. Although numerous studies have confirmed that DREB2s contribute greatly to the enhanced drought and salinity tolerance of a plant (Chen et al, 2009;Matsukura et al, 2010;Li et al, 2017), few studies have focused on the bacterial communities in the soil of plants modified by DREB2s (Chunmiao et al, 2015). Therefore, it is important to evaluate the influence of plants modified with DREB2 genes on hormone processes that could influence the root-associated bacterial communities.…”
Section: Introductionmentioning
confidence: 99%
“…There are several aspects of the plant response to drought, such as sensing stress, activating systemic signaling pathways, and genetically regulating the responses (Zolla et al, 2013). Many genes involved in plant responses to drought have been identified, and some of these have been effectively used to improve drought tolerance (Gosti et al, 1995;Iuchi et al, 2001;Li et al, 2017) by developing new drought-tolerant crop varieties through genetic modifications to increase crop productivity and reduce costs (Romão-Dumaresq et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Further, fungal community structure and diversity are affected by many environmental variables (Yang et al, 2017). Although DREB2s are known to contribute greatly to enhance drought and salinity tolerance in plants (Chen et al, 2009;Matsukura et al, 2010;Li et al, 2017), few studies have focused on the fungal communities in the soil of TG plants harboring DREBs (Yu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%